The Public Service Agency (BLU) Paradox: Why Budget Achievements Don’t Always Reflect Superior Performance - Hitijahubessy, Martha Maria; Borolla, Johanis Darwin; Tetelepta, Silva (Accounting Research Unit (ARU Journal), 2025)
This study aims to critically examine the financial performance of Pattimura University under the Public Service Agency (BLU) framework during the 2019–2024 period. Specifically, it investigates the university’s fiscal independence, budget effectiveness, and operational efficiency to assess the extent to which financial flexibility translates into institutional advancement. Quantitative data analysis reveals consistently high effectiveness in revenue realization and exceptional operational efficiency—indicating strong financial discipline. However, the fiscal independence ratio remained modest, fluctuating between 35% and 45%, and dropped to its lowest point in 2024. This modest fiscal independence highlights the need for improvement in this area. More importantly, despite these favorable financial metrics, Pattimura University continues to hold a B level institutional accreditation. This discrepancy illustrates a core paradox: robust financial performance under the BLU model does not automatically lead to superior academic or institutional outcomes. The findings suggest that financial autonomy, while necessary, is insufficient unless integrated with strategic investment in academic quality, research capacity, and institutional governance.